2019
DOI: 10.1038/s41467-019-09041-z
|View full text |Cite
|
Sign up to set email alerts
|

The molecular logic of Nanog-induced self-renewal in mouse embryonic stem cells

Abstract: Transcription factor networks, together with histone modifications and signalling pathways, underlie the establishment and maintenance of gene regulatory architectures associated with the molecular identity of each cell type. However, how master transcription factors individually impact the epigenomic landscape and orchestrate the behaviour of regulatory networks under different environmental constraints is only partially understood. Here, we show that the transcription factor Nanog deploys multiple distinct m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 60 publications
7
92
0
Order By: Relevance
“…Accordingly, NANOG binding was strongly enriched at loci whose accessibility was upregulated in OCT4‐high or SOX2‐high cells compared to regions with downregulated accessibility (Fig EV5N). This suggests that NANOG may act as a binding partner to regulate chromatin accessibility at these loci, in line with a recent study (Heurtier et al , ). Loci with increased accessibility in OCT4‐high cells lose accessibility upon rapid OCT4 depletion (data from King & Klose, ), in line with OCT4 directly regulating accessibility at these sites (Fig EV5O) even though we cannot exclude that some loci may be regulated by indirect mechanisms.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Accordingly, NANOG binding was strongly enriched at loci whose accessibility was upregulated in OCT4‐high or SOX2‐high cells compared to regions with downregulated accessibility (Fig EV5N). This suggests that NANOG may act as a binding partner to regulate chromatin accessibility at these loci, in line with a recent study (Heurtier et al , ). Loci with increased accessibility in OCT4‐high cells lose accessibility upon rapid OCT4 depletion (data from King & Klose, ), in line with OCT4 directly regulating accessibility at these sites (Fig EV5O) even though we cannot exclude that some loci may be regulated by indirect mechanisms.…”
Section: Resultssupporting
confidence: 90%
“…Using thousands of ChIP‐seq datasets in ES cells, we could train a model to predict, with relatively good accuracy, regions that were upregulated or downregulated in accessibility upon high levels of OCT4 or SOX2 (Fig EV5M). We identified NANOG binding as enriched in upregulated regions, consistent with a recent report on the impact of NANOG depletion on OCT4/SOX2 binding and accessibility (Heurtier et al , ). However, we could not find features allowing to predict whether loci are more dependent on OCT4 versus SOX2.…”
Section: Discussionsupporting
confidence: 91%
“…To validate preliminary NANOG-responsive genes from this analysis, we further performed a complementary analysis followed by filtering to include only genes that have been previously identified as responding to NANOG [34][35][36][37][38] . Subsequently, we acquired the refined NANOG-responsive six genes (FGFBP1, SPESP1, HMGA2, PERP, FGF1, and DKK1).…”
Section: Resultsmentioning
confidence: 99%
“…In common with some other pluripotency TFs expressed in naïve pre-implantation cells, NANOG is not expressed during peri-implantation development [15,38], nor in EpiLCs [12,28]. Previous work has demonstrated that NANOG and OTX2 work antagonistically in ESCs [27,39] and OTX2 has been shown to be robustly expressed in both EpiLCs and the peri-implantation epiblast [17,24]. However, OTX2 is not responsible for ongoing repression of Nanog in EpiLCs [17].…”
Section: Questions For the Futurementioning
confidence: 98%